Results of interlaboratory comparison tests of geosynthetic material - A. V. Kozlov (Vestnik MGSU)
Introduction. The relevance of the study is determined by the need to improve the procedure of construction control of road-building materials in terms of laboratory tests. One of the effective methods of checking the competence of the laboratory is interlaboratory comparative tests. The purpose of their implementation is to detect deficiencies and inconsistencies, analyze the causes of their occurrence, carry out corrective measures and, thus, improve the laboratory quality system.Materials and methods. Geogrid was taken as the object of research. The results of tensile strength, relative elongation at maximum load, as well as indicators of frost resistance of the material and resistance to ultraviolet radiation were selected for interlaboratory comparison. All tests were performed in the longitudinal direction of geogrid samples. The most and least statistically homogeneous physical and mechanical parameters of geogrids were determined under the conditions of reproducibility of measurement results for each of the indices obtained in different laboratories and by various measuring instruments using an algorithm based on Z-scores.Results. According to the totality of the test results, the quality of the work of the majority of testing laboratories can be considered as satisfactory. Representative data were obtained for the majority of parameters. No unsatisfactory data were found in the context of parameters; the share of satisfactory results is 87.5–100 %.Conclusions. The permormance-test data indicate a high level of competence of the participants in the interlaboratory comparisons. Participation in interlaboratory comparison programmes is undoubtedly an effective way to verify and improve the quality of tests; individual analysis of the results makes it possible to improve the laboratory quality system. It seems reasonable to normalize the requirements for the coefficient of variation, convergence and reproducibility of controlled parameters.